Effect of common storage temperatures and container types on urine protein : creatinine ratios in urine samples of proteinuric dogs. (17th September 2018) - Moyle, Patrick S.; Specht, Andrew; Hill, Richard
Abstract : Background: Preanalytic protein adsorption to polymer and glass container surfaces may decrease urine protein concentration measurements and urine protein: creatinine ratios (UPC). Hypothesis/Objectives: Urine stored in PC or glass containers will have lower UPC than urine stored in HP containers. The specific objective was to determine whether clinically relevant differences in UPC would be detected after storage in glass, PC, or HP containers using common storage times and temperatures. Animals: Twelve client‐owned dogs with proteinuria. Methods: Prospective, nonmasked study, divided into 2 phases. The first phase was a pilot study involving multiple (n = 5) measurements at each storage condition using 24‐hours urine samples from 2 dogs with persistent renal proteinuria of different magnitude. The second phase used urine samples from 10 dogs with proteinuria of variable magnitude. Sample aliquots were stored in HP, PC, and glass containers at 24°C for 4 hours, 4°C for 12 hours, and −20°C for 72 hours. The UPC of each was measured after storage and compared with baseline. Results: Statistically significant but clinically irrelevant differences were found in phase 1. In phase 2, storage conditions did not affect urinary protein or creatinine concentrations or UPC. Conclusions and Clinical Importance: Collection and storage of canine urine samples in clean HP, PC, or glass containers at 24°C for 4 hours, 4°C for 12 hours, or −20°C for 72 hours is unlikely to result in clinically relevant decreases in measured UPC values.